Design, modeling, and analysis of a high performance piezoelectric energy harvester for intelligent tires. (8th March 2019) - Esmaeeli, Roja; Aliniagerdroudbari, Haniph; Hashemi, Seyed Reza; Alhadri, Muapper; Zakri, Waleed; Batur, Celal; Farhad, Siamak
Summary: Basic parameters affecting vehicle safety and performance such as pressure, temperature, friction coefficient, and contact‐patch dimensions are measured in intelligent tires via sensors that require electric power for operation and wireless communication to be synchronized to the vehicle monitoring and control system. Piezoelectric energy harvesters (PEHs) can extract a fraction of energy that is wasted as a result of deflection during rolling of tires, and this extracted energy can be used to power up sensors embedded in intelligent tires. A new design of PEH inspired from Cymbal PEHs is introduced, and its performance is evaluated in this paper. Cymbal PEHs are proven to be useful in vibration energy harvesting, and in this paper, for the first time, the modified shape of Cymbal energy harvester is used as strain‐based energy harvester for the tire application. The shape of the harvester is adjusted in a way that it can be safely embedded on the inner surface of tires. In addition to the high performance, ease of manufacturing is another advantage of this new design. A multiphysics model is developed and validated to determine the output voltage, power, and energy of the designed PEH. The modeling results indicated that the maximum output voltage, the maximum electric power, and the accumulated harvested energy are about 3.5 V, 2.8 mW, and 24 mJ/rev, respectively, which are sufficient to power two sensors. In addition, the possibility is shown to supply power to five sensors by increase in piezoelectric material thickness. The effect of rolling tire temperature on the performance of the proposed PEH is also studied. Abstract : Multiphysics modeling have been conducted on a new shape of piezoelectric energy harvester for tire waste strain energy harvesting. The analysis was carried out under varying energy harvester width, thickness, and rolling tire temperature. The potential is shown in the proposed energy harvester to supply enough energy for two tire sensors and can supply to five sensors by increase in piezoelectric material thickness. The results have illustrated that by increase in the air temperature inside the tire, the generated energy increase about 8.6%.